CORRECTION MOTOR-SECRETORY DISORDERS IN GASTROESOPHAGEAL REFLUX DISEASE ASSOCIATED WITH IRON DEFICIENCY ANEMIA IN YOUNG ADULTS - Shapovalova, O. (World of Medicine and Biology, 2013)
It is found that the students of GERD patients with IDA marked increase gastrin, reduced melatonin levels and quality of life, which are together in close correlation, and all of these indicators above and below not only comparison with the control group, but the data studies in patients with GERD without comorbidities. It is also found that the inclusion of a standard scheme dalargina contributes to the quality of life, reducing the timing of clinical remmisii, melatonin levels rise and pronounced reduction of gastrin.
Keywords: gastroesophageal reflux disease; iron deficiency anemia; the quality of life